2011
DOI: 10.1016/j.molmed.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the TCA cycle: signaling to tumor formation

Abstract: A role for mitochondria in tumor formation is suggested by mutations in enzymes of the TCA cycle: isocitrate dehydrogenase (IDH), succinate dehydrogenase (SDH) and fumarate hydratase (FH). Although they are all components of the TCA cycle, the resulting clinical presentations do not overlap. Activation of the hypoxia pathway can explain SDH phenotypes, but recent data suggest that FH and IDH mutations lead to tumor formation by repressing cellular differentiation. Here we discuss recent findings in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
184
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(186 citation statements)
references
References 67 publications
1
184
0
1
Order By: Relevance
“…Although the source of 2-HG is not fully understood, experimental evidences indicate that IDH1 and IDH2 have a role in the production of d-2-HG (Matsunaga et al, 2012). d-2-HG and its enantiomer l-2-HG are linked to the Krebs cycle (Raimundo et al, 2011) and are found to be elevated in certain types of cancer (Dang et al, 2009;Rakheja et al, 2011) and in different variants of the neurometabolic 2-hydroxyglutaric aciduria. In relation to the latter defect, a recent study from Nota et al (2013) reported 12 recessive mutations (Ser193Trp, Arg282Gly, Arg282Cys, Gly167Arg, Pro45Leu, Glu144Gln, Met202Thr, Tyr297Cys, Tyr256*, Ala9Profs*82, A274Ilefs*24, and Arg173Glyfs*2) found in the CIC gene of three individuals and their families that cause combined d-2-and l-2-hydroxyglutaric aciduria.…”
Section: Citrate In Neurodevelopmental Syndromes and Hydroxyglutaricmentioning
confidence: 99%
“…Although the source of 2-HG is not fully understood, experimental evidences indicate that IDH1 and IDH2 have a role in the production of d-2-HG (Matsunaga et al, 2012). d-2-HG and its enantiomer l-2-HG are linked to the Krebs cycle (Raimundo et al, 2011) and are found to be elevated in certain types of cancer (Dang et al, 2009;Rakheja et al, 2011) and in different variants of the neurometabolic 2-hydroxyglutaric aciduria. In relation to the latter defect, a recent study from Nota et al (2013) reported 12 recessive mutations (Ser193Trp, Arg282Gly, Arg282Cys, Gly167Arg, Pro45Leu, Glu144Gln, Met202Thr, Tyr297Cys, Tyr256*, Ala9Profs*82, A274Ilefs*24, and Arg173Glyfs*2) found in the CIC gene of three individuals and their families that cause combined d-2-and l-2-hydroxyglutaric aciduria.…”
Section: Citrate In Neurodevelopmental Syndromes and Hydroxyglutaricmentioning
confidence: 99%
“…[12][13][14] The currently known mechanisms underlying tumorigenesis linked to defects in the TCA cycle are well reviewed. 15,16 Defects in the SDH, FH, and IDH genes inhibit prolyl hydroxylases, leading to decreased hydroxylation of hypoxia-inducible factor-α. This results in activation of the hypoxia pathway, which supports tumor formation by activating angiogenesis, glucose metabolism, cell motility, and cell survival.…”
Section: © American College Of Medical Genetics and Genomicsmentioning
confidence: 99%
“…28,29 High oxygen consumption through mitochondrial respiration was observed in shCont cells. Nonetheless, reduction of PP2A Cα led to suppressed mitochondrial respiratory capacity at the basal and maximal level.…”
Section: Discussionmentioning
confidence: 99%